A Novel Small Sierpenski Antennas - Abdelhak Ferchichi; Gharsallah Ali (Institute of Advanced Engineering and Science, 2013)
In This paper, new small antenna is described and it is designed to be used in RFID applications at microwave frequencies. This structure represents a new version of sierpenski antenna. The reduction of size by more than 75% gives this patch a great inters. Two equivalent resonant models are presented based on a model of triangular and sierpenski patch antennas.DOI:http://dx.doi.org/10.11591/ijece.v3i4.2580